If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -9 = 24x + 3 Reorder the terms: -9 + 6x = 24x + 3 Reorder the terms: -9 + 6x = 3 + 24x Solving -9 + 6x = 3 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. -9 + 6x + -24x = 3 + 24x + -24x Combine like terms: 6x + -24x = -18x -9 + -18x = 3 + 24x + -24x Combine like terms: 24x + -24x = 0 -9 + -18x = 3 + 0 -9 + -18x = 3 Add '9' to each side of the equation. -9 + 9 + -18x = 3 + 9 Combine like terms: -9 + 9 = 0 0 + -18x = 3 + 9 -18x = 3 + 9 Combine like terms: 3 + 9 = 12 -18x = 12 Divide each side by '-18'. x = -0.6666666667 Simplifying x = -0.6666666667
| V-7v=12 | | 15=4(x-3)-(x-9) | | 9=-5n+1+3 | | 4x^2-4x+7x-7=2x-1 | | -4+9(6y+3)=(4y-5)-4 | | 4(x-5)+12=8 | | 32x+4y=0 | | f(x)=50cos(7*(x^6)) | | (x+1)(3x+1)=96x^2 | | 16+5(6c-3)= | | x(x+1)=x(x+1)+5 | | 5ab+8ab= | | 2[7-(-4x-5)]=32x+54 | | 5x+4x+4=x+6x+16 | | T=(7+RS) | | T=(7+RS)forS | | -8+5u=-33 | | 8x+a-12=4x-13-5x | | 5t(9t+4)=0 | | s=4k+4 | | 8t+6=6+7t | | (4z+5)(3-z)=0 | | 13x+24x-31x=144 | | 7y+2=6y-2 | | 3x^2-12x-180=0 | | 3y+8=2y-6 | | 2x^2-6x+14=0 | | 3x^7-243=0 | | 2x+10y+(-10y)+(-10x)= | | 193.6=m(10000)+b | | 2b-15=-25 | | -x=.63 |